2018
DOI: 10.1016/j.envpol.2017.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of offshore oil spills on polar bears in the Chukchi Sea

Abstract: a b s t r a c tSea ice decline is anticipated to increase human access to the Arctic Ocean allowing for offshore oil and gas development in once inaccessible areas. Given the potential negative consequences of an oil spill on marine wildlife populations in the Arctic, it is important to understand the magnitude of impact a large spill could have on wildlife to inform response planning efforts. In this study we simulated oil spills that released 25,000 barrels of oil for 30 days in autumn originating from two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Indigenous peoples inhabit some of the most ecologically undisturbed areas of the world, often of outstanding biodiversity importance (Garnett et al 2018). Thus, pollution in IP lands has an uneven and significant impact on critical environments, affecting large numbers of wildlife species (Basu et al 2009; Wilson et al 2018). While the impacts of pollution on ecosystems and biodiversity have been studied extensively (Taylor et al 2016), particularly in aquatic systems (Desforges et al 2018), accumulated evidence of these impacts comes primarily from industrialized nations, with a strong focus on consequences of agricultural intensification and industrialization.…”
Section: Resultsmentioning
confidence: 99%
“…Indigenous peoples inhabit some of the most ecologically undisturbed areas of the world, often of outstanding biodiversity importance (Garnett et al 2018). Thus, pollution in IP lands has an uneven and significant impact on critical environments, affecting large numbers of wildlife species (Basu et al 2009; Wilson et al 2018). While the impacts of pollution on ecosystems and biodiversity have been studied extensively (Taylor et al 2016), particularly in aquatic systems (Desforges et al 2018), accumulated evidence of these impacts comes primarily from industrialized nations, with a strong focus on consequences of agricultural intensification and industrialization.…”
Section: Resultsmentioning
confidence: 99%
“…PACs biodilute, which means that their concentrations decrease with higher trophic level due to the increase of biotransformation rate (De Laender et al, 2011). Recently, modelling of oil spill's impact on polar bears was calculated and it was found that around 27-38 % of polar bears from the Chukchi sea region would be affected (Wilson et al, 2018). Indeed, it was noted that oil spills could probably reach important habitats for polar bears, such as areas of denning or summer terrestrial habitats (Wilson et al, 2018).…”
Section: Pacs Have Not Been Measured In Polar Bearsmentioning
confidence: 99%
“…Oil spills in the Arctic will affect the entire food web. Model studies suggest, for example, that oil spills can expose large fractions of populations of polar bears to released oil in the Chukchi Sea (Wilson et al 2018) and causes different risks to other animals, like ringed seals and walrus, based on an oil spill risk assessment for the Kara Sea (Helle et al 2020). Arctic sea birds are also sensitive to oil pollution as demonstrated in the high mortality of guillemots and little auks off Newfoundland caused by ship-source oil pollution (Frederiksen et al 2019).…”
Section: Introductionmentioning
confidence: 99%